Implications of Single-Step Graphitization For Reconstructing Late Holocene Relative Sea-Level Using Radiocarbon-Dated Organic Coastal Sediment - Sefton, Juliet P.; Kemp, Andrew C.; Elder, Kathryn L.; Hansman, Roberta L.; Roberts, Mark L. (Radiocarbon, 2022)
Late Holocene relative sea-level reconstructions are commonly generated using proxies preserved in salt-marsh and mangrove sediment. These depositional environments provide abundant material for radiocarbon dating in the form of identifiable macrofossils (salt marshes) and bulk organic sediment (mangroves). We explore if single-step graphitization of these samples in preparation for radiocarbon dating can increase the number and temporal resolution of relative sea-level reconstructions without a corresponding increase in cost. Dating of salt-marsh macrofossils from the northeastern United States and bulk mangrove sediment from the Federated States of Micronesia indicates that single-step graphitization generates radiocarbon ages that are indistinguishable from replicates prepared using traditional graphitization, but with a modest increase in error (mean/maximum of 6.25/15 additional 14C yr for salt-marsh macrofossils). Low 12C currents measured on bulk mangrove sediment following single-step graphitization likely render them unreliable despite their apparent accuracy. Simulated chronologies for six salt-marsh cores indicate that having twice as many radiocarbon dates (since single-step graphitization costs ∼50% of traditional graphitization) results in narrower confidence intervals for sample age estimated by age-depth models when the additional error from the single-step method is less than ∼50 14C yr (∼30 14C yr if the chronology also utilizes historical age markers). Since these thresholds are greater than our empirical estimates of the additional error, we conclude that adopting single-step graphitization for radiocarbon measurements on plant macrofossils is likely to increase precision of age-depth models by more than 20/10% (without/with historical age markers). This improvement can be implemented without additional cost.
Keywords: age-depth model; mangrove; Massachusetts; Micronesia; Salt marsh